Clinical and morphological characteristics of placentas of full-term infants with congenital infectious diseases - A. V. Agafonova; V. V. Vasiliev; N. V. Rogozina (Детские инфекции (Москва), 2022)
Materials and methods. The features of the course of pregnancy and childbirth, the condition of children at birth, histomorphological conclusions of placentas and the expression of the CD15 marker in the placentas of 40 children with congenital infectious diseases, 10 children with asphyxia at birth and 10 healthy full-term children were analyzed.Results. The analysis showed the absence of reliable clinical and morphological criteria for the risk of developing a congenital infectious disease. Thus, the majority of mothers of children of all comparison groups had various somatic pathology: 33 (82.5%) in group 1, 8 (80%) in group 2, 6 (60%) in group 3 (p ≥ 0.05) Children of all comparison groups were statistically comparable in gestational age, anthropometric data and assessment on the Apgar scale. During histological examination, inflammatory changes in the afterbirth in children of the compared groups were recorded with almost the same frequency: in 17 (42.5%) children with intrauterine infection, 4 (40%) with asphyxia at birth and 2 (20%) healthy children (p ≥ 0.05). At the same time, immunohistochemically, placentas of children with congenital infectious diseases were characterized by a significantly higher level of CD15 expression compared to placentas of healthy children: CD15 expression coefficient in placentas of children with congenital infectious diseases was 6.9 ± 0.9, in the group of healthy children — 0.7 ± 0.5, (p < 0.05).Conclusion. The use of the immunohistochemical marker CD15 makes it possible to predict congenital infectious disease in newborns in the absence of obvious morphological signs of an infectious lesion of the afterbirth, and can be used to form risk groups for the implementation of infectious pathology.